'A STORY OF "BAQAROH": A JUSTIFICATION OF THE ISRAILIAN ANOMALY AND DISOBIDIANCE' - Afrizal Nur (AL-FIKRA, 2014)
The  Our'anis referencefor   human  beings  to  see   the  historyoj human   civilization  in   ancient   time,    inciudinq  the    history  ofthe Jewishpeople.TheJews   have  atraditionofbadfaith  alwaysdeviate from    "Tauhid"  (monotheism),  this   condition  is  commonand   has become  a  habitthathas   taken  holdofmany  generations.  Practices ofidolatry,  paganism,    anomaly  form    sand     other    disobediences, whichisatraditionthat  regeneratesand  will  continueinhibittothe Jews.  Bani  Israilalso  did  notobey  tothe  treatisewhichbroughtthe prophet    Moses.   Deviating   conception   (anomalous),   their    bad qualitiessuch   ashostile,stubborn,hard-hearted,  brokenpromises, grabber,greedy  and   others,  have   repeatedly  told   by  God  inthe Qur'an:Messagefrom   surah  al-Baqarah  verse   67isthe  evidence that  justifies   how   bad   character  of  Bani   Israil.  PhilosopherKarl Marx  said:"TheJew   can  only  befree   when   their  habitualattitude nolongermaintained"